Rekonstruksi Hukum Perlindungan Hak Istimewa Adat Papua Dalam Program Strategis Nasional - Silehu, M Iqbal (Faculty of Law, University of Muhammadiyaha Surabaya, 2025)
The National Strategic Program is part of the national interest in terms of economic and infrastructure development, regulated through Presidential Regulation No.03/2016 on the Acceleration of the Implementation of National Strategic Projects. However, this National Strategic Project scheme faces polemics related to the denial of the privileges of indigenous peoples, as happened in Merauke. So that the problems that occur have legal implications, namely violating the customary rights of the people in the Papua region. This study formulates the problem, namely how the government's authority in managing customary land for development in Indonesia and how the ideal regulation of customary land management in Papua for development in the National Strategic Program based on the Responsive Law perspective. This type of research is Normative Juridical and uses a statute approach and conceptual approach. The results of the study show that government policies are still Repressive law and override the rights of indigenous Papuans.